The Efficiency of Rice Production Analysis in The Western Part of Indonesia By Using Stochastic Frontier Analysis Method (SFA) - Yuli Eni, Lili Tri Enjelia, Juliani Margaretha Putri, Felia Novita Sari (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to measure the level of efficiency and factors that affect the agricultural industry in fifteen regions of western Indonesia specifically for rice farming. To determine the level of efficiency of the rice industry from fifteen provinces in Indonesia, efficiency studies were carried out using the Stochastic Frontier Analysis (SFA) method. SFA is one of the parametric methods used to calculate the relative efficiency level. To find out the factors that need to be done with the Regression method. The study was conducted using output and input data from 15 provinces in the western part of Indonesia in 2018. This data collection was obtained from the Ministry of Agriculture Data Center. The results of this study found that the internal factors of land area and tractor machinery affect the efficiency of rice production. While on external factors found external factors pests and droughts to the efficiency of rice production.